Doing it by the book : training student teaching at the Faculty of Letters, the University of Porto (FLUP) to evaluate English Language Teaching (ELT) materials - Hurst, Nicolas (2015)
Understanding what the use of a coursebook implies is at the heart of any consideration of how ELT instruction in Portugal operates and, as such, should also be central to any pre-service teacher education. Since the curricular reorganization prompted by the 'Bologna Process', the Faculty of Letters, the University of Porto (FLUP) has included within its 'Masters in English and other Foreign Language Teaching' course (Mestrado em Ensino de Inglês e de Alemão / Francês / Espanhol no 3.º ciclo do Ensino Básico e no Ensino Secundário) an optional, one semester subject called the "Production of Didactic Materials". This talk will demonstrate and discuss how, in this case, training student teachers to develop a criteria based framework for evaluating FL teaching materials, and applying that same framework, can be considered a way of re-focusing the traditionally, largely theoretical, lecture-based training courses typical of the Portuguese paradigm.